Legal Consequences of The Separation of the Chagos Archipelago from Mauritius in 1965 (ICJ Advisory Opinion, 25 February 2019, General List No. 169) - Rrecaj, Besfort T. (Utrecht Journal of International and European Law, 2020)
On 25 February 2019 the International Court of Justice (ICJ or the Court) issued its advisory opinion on legal consequences of the separation of the Chagos Archipelago from Mauritius in 1965. The request for the advisory opinion was made by the United Nations General Assembly (UNGA) through its Resolution 71/292. The Resolution adopted on 22 June 2017 with 94 votes in favor, 15 against and 65 abstantions. The Court held unanimously that it has jurisdiction to give the advisory opinion as requested and by 13 votes to one decided that the detachment of the Chagos Archipelago immediately before the final stage of decolonization was wrongful thus violating international law and specifically the right to self-determination. Inter alia the court was of the opinion that the agreement between the United Kingdom of Great Britain and Northern Ireland (United Kingdom) and Mauritius concluded in 1965 leaving Chagos Archipelago under administration of United Kingdom after completion of decolonization was flawed because it lacked the free expression of the will of the people on the side of Mauritius. Therefore according to the Court the United Kingdom is obliged to bring to an end its administration over Chagos Archipelago as rapidly as possible and that all members states are obliged to cooperate in the process. Eight judges presented their declarations among whom two presented a joint declaration, four judges presented separate opinions and one of the judges presented a dissenting opinion at the end of the proceedings. Thirty three states have submitted written statements. In addition the African Union organization was allowed to submit written statement. Eleven state have submitted comments related to written statements and 23 states have presented their oral argument before the ICJ. The Chagos Archipelago is located in the Indian Ocean about 500 km from the Maldives archipelago.